1994
DOI: 10.1113/jphysiol.1994.sp020353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin II on intracellular Ca2+ and pH in isolated beating rabbit hearts and myocytes loaded with the indicator indo‐1.

Abstract: 1. Angiotensin II increases myocardial contractility in several species, including the rabbit and man. However, it is controversial whether the predominant mechanism is an increase in free cytosolic [Ca2+]i or a change in myofilament Ca"+ sensitivity. To address this question, we infused angiotensin II in isolated perfused rabbit hearts loaded with the Ca2" indicator indo-1 AM and measured changes in beat-to-beat surface transients of the Ca"+-sensitive 400 500 nm ratio and left ventricular contractility. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 43 publications
4
59
2
Order By: Relevance
“…-sensitivity in cardiac muscle (1,5). One of the explanations of the present study is that Rho/ ROCK pathways also regulate the Ca…”
Section: +mentioning
confidence: 87%
See 2 more Smart Citations
“…-sensitivity in cardiac muscle (1,5). One of the explanations of the present study is that Rho/ ROCK pathways also regulate the Ca…”
Section: +mentioning
confidence: 87%
“…Although earlier reports suggest the involvement of increased Ca 2+ influx through L-type Ca 2+ channels (3,4) and increase in Ca 2+ sensitivity of myofibrils (5), the intracellular mechanisms leading to these changes have not yet been clarified. These vasoconstrictive agonists are also known to play a role in the development of cardiac hypertrophy or heart failure (6,7).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…These second messengers subsequently promote inotropy by increasing sarcolemmal I Ca 2+ and [Ca 2+ ] I , and by alkalinizing cardiomyocytes via protein kinase C (PKC) activation of the Na + /H + exchanger. 7,[13][14][15][16] The role of AT 2 receptors is less clear, but they have been shown to act in vasodilation, in part through nitric oxide-cGMP signaling. 7 We and others have shown that angiotensin II improves inotropy in normal rat hearts during conditions of acidosis.…”
Section: Effects Of Acute Angiotensin II On Ischemia Reperfusion Injumentioning
confidence: 99%
“…In single cells, AIl may increase cl+ via direct modulation of the L-type channels (Baker et al 1989). However, other studies have shown that the inotropic effect is secondary to an intracellular alkalosis and increased myofilament Ca 2 + sensitivity (Ikenouchi et al 1994). Our aim was to determine whether the functional response to AIl stimulation in the intact, beating heart was caused by a significant change in intracellular pH (pHi)' New Zealand White rabbits were anaesthetized using Hypnorm (0'3 ml (kg body wtfi, LM .)…”
Section: Department Of Biochemistry and * University Laboratory Ofmentioning
confidence: 99%